Phase evolution and dielectric properties of barium zirconate titanate - Barium iron niobate ceramics - Uraiwan Intatha (2018)
The structural and dielectric properties of (1-x)BaZr0.9Ti0.1O3(BZT) - xBaFe0.5Nb0.5O3(BFN) ceramics system were investigated as a function of the BaFe0.5Nb0.5O3content by X-ray diffraction (XRD) and dielectric measurement technique. Studies were performed on the samples prepared by solid state reaction for x = 0.2, 0.4, 0.6 and 0.8. Maximum density of the ceramic was obtained at 1450°C for every mixing conditions. The evolution of the tetragonal phase, indicating phase transition from cubic to tetragonal with increasing with BFN ratio. Lattice parameters were found to decrease with the BFN content. The dielectric properties of (1-x)BZT - xBFN ceramics were studied. It was found that the dielectric constant and broadness of their peak of these ceramics increased with increasing BFN contents, with the dielectric loss measured at 1 kHz was shown lower than 2.00 at working temperature ranging from room temperature to 400°C. Copyright © Taylor & Francis Group, LLC.